Wpływ koncepcji sprawiedliwości Chaima Perelmana na dokonywane dzisiaj rozstrzygnięcia Trybunału Konstytucyjnego - Śmieja, Piotr Szymon (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article discusses Chaim Perelman’s conception of justice proposed in 1945. His concept is a continuation of Aristotle’s and St. Thomas Aquinas’s views, however, it rejects emotional load and formulates a theory through six keyword terms instead. The core foundation of using proposed formulas is the order to treat people that belong to the same social category equally, and this warrant is crucial to act rightly. The article includes thoughts on who, to whom and in which way should distribute what is someone’s due. Perelman notices that using these formulas is relative and mathematically impossible, what leads him to the conclusion that the final decision should depend on the judge’s righteousness. There is a risk of applying justice in such a form as it consists of subjective perception of reality that creates room for manipulation.